On-chip correlation-based Brillouin sensing: Design, experiment, and simulation - Zarifi, Atiyeh; Stiller, Birgit; Merklein, Moritz; Liu, Yang; Morrison, Blair; Casas-Bedoya, Alvaro; Ren, Guanghui; Nguyen, Thach G.; Vu, Khu; Choi, Duk-Yong; Mitchell, Arnan; Madden, Steven J.; et al. (Journal of the Optical Society of America B-Optical Physics, 2019)
Wavelength-scale stimulated Brillouin scattering (SBS) waveguides are enabling novel on-chip functionalities. The microscale and nanoscale SBS structures and the complexity of the SBS waveguides require a characterization technique to monitor the local geometry-dependent SBS responses along the waveguide. In this work, we demonstrate an experimental spatial resolution of 500 μm, which can detect feature sizes down to 200 μm on a silicon–chalcogenide photonic waveguide using the Brillouin optical correlation domain analysis technique. We provide extensive simulation and analysis of how multiple acoustic and optical modes associated with geometrical variations influence the Brillouin spectrum.
CRIS-Team Scopus Importer:2021-06-29